BET 2: Probiotics and crying time in babies with infantile colic. Issue 7 (19th June 2015) - Batchelor, Nina; Kelly, Jennifer; Choi, Hyun; Geary, Brona
Abstract : A short-cut review was carried out to establish whether probiotics reduced crying time in babies with infantile colic. Using the reported searches 88 papers were found, of which five presented the best evidence to answer the clinical question. The author, date and country of publication, patient group studied, study type, relevant outcomes, results and study weaknesses of the best papers are tabulated. It is concluded that there is evidence that the administration of probiotics decreases the severity and duration of infantile colic when compared with placebo and some proprietary remedies.